ROMERO, Joan (2009). Geopolítica y gobierno del territorio en España - Parés, Marc (Documents d'Anàlisi Geogràfica, 2010)
ROMERO, Joan (2009) Geopolítica y gobierno del territorio en España València: Tirant lo Blanch; 273 p. ISBN 13: 978-84-98764-78-9